A microreactor with metallic catalyst support for hydrogen production by partial oxidation of dimethyl ether - Kim, Do Hyung; Kim, Sang Hoon; Byun, Ji Young (ELSEVIER SCIENCE SA, 2015)
A microreactor system with porous metallic catalyst support was prepared and its catalytic efficiency and long term stability were compared with those of a conventional pack bed reactor using partial oxidation of DME for production of hydrogen. The microreactor system had a thin layer of gamma-Al2O3 on FeCrAl metal foam as catalyst support. The pack bed reactor had gamma-Al2O3 balls densely packed in a quartz tube. With enough catalyst materials (0.5 wt% Rh), both of the reactors showed good hydrogen yield higher than 90% at reaction temperature up to 750 degrees C. However, with decreasing Rh content, the pack bed reactor showed deteriorating reaction efficiency while the microreactor maintained the efficiency. In the end, in order to maintain similar reaction efficiency for long term hydrogen production, 10 times more Rh content was necessary for the pack bed reactor than that needed for the microreactor. The pack bed reactor maintained hydrogen production only up to about 120h, while the microreactor maintained hydrogen production up to 1200 h, 10 times longer than that of pack bed reactors. This comparison shows superior reaction efficiency and stability of metallic support loaded microreactors over conventional ceramic support loaded pack bed reactors for exothermic and high temperature reactions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: SOLID-ACID CATALYSTS; COMPOSITE CATALYSTS; ANODIC-OXIDATION; NATURAL-GAS; FUEL-CELLS; ALUMINA; METHANE; DME; COPPER; CU